Regulation of galactose oxidase synthesis and secretion in Dactylium dendroides: effects of pH and culture density. - Shatzman, A R (1977)
The effects of pH and growth density on the amount of an extracellular enzyme, galactose oxidase, synthesized by the fungus Dactylium dendroides were studied. Growth at a pH below 6.7 caused a decrease in the ability of the organism to release galactose oxidase. The enzyme retained by these fungal cells was liberated whenever the pH was raised to 7.0. Cycloheximide addition failed to inhibit the appearance of this protein; [3H]leucine added prior to pH adjustment was not incorporated into the released protein, These observations indicate the released protein is not newly synthesized protein. The retained enzyme would be secreted slowly over a 2-day period if the pH was not increased. In addition to regulating protein retention, pH was also shown to be associated with vacuolization, cell volume, culture density, and inhibition of protein synthesis. Cultures maintained at low pH were characterized by a dense growth consisting of highly vacuolated, buoyant, fungal hyphae. Increasing the pH from 6 to 7 caused a decrease in vacuole size. Cells grown at neutral pH maintained a lower density of growth and, based on activity measurements, synthesized 33% more galactose oxidase. Furthermore, cultures grown at pH 6.0 and maintained at a lower cell density produced galactose oxidase at a level similar to that of cells grown at neutral pH. Thus, the elevated density of the cell culture was inhibitory to galactose oxidase synthesis. The observed effects on protein synthesis and release were rather specific for galactose oxidase, since other extracellular proteins appeared in the earliest stages of growth.